Actinomycosis of male breast: a rare case report - Mahadik, Abhishek; Rajakumar, Rontgen; Khan, Nida; Singhal, Pragati (International Surgery Journal, 2020)
Actinomyces is a commensal of gastrointestinal and genital tract that may cause subacute or chronic granulomatous inflammation. Primary actinomycosis of breast is an extremely rare disease. It may present as a mass or as discharging fistulae. It is often diagnosed after biopsy. It may mimic inflammatory carcinoma or mastitis. Treatment is with a prolonged course of antibiotic. Authors present a case of a 70-year-old male with a palpable breast lump, that was suspected to be malignant. Wide local excision was performed, histopathology confirmed the diagnosis of actinomycoses breast. Patient was given antibiotics post operatively.